Exploring the experiences and outcomes of children and young people receiving support for special educational needs over time in England: a qualitative study - Saxton, Jennifer; Matthews, Jacob; Winterburn, Isaac; Casey, Helen; Zylbersztejn, Ania; Barnes, Sarah; Hall, Poppy; Tripp, Charlotte; Black-Hawkins, Kristine; Ford, Tamsin (Frontiers in Education, 2025)
BackgroundOne in five school-aged children and young people (CYP) in England are identified as having a special educational need or disability (SEND) requiring additional support. Despite growing numbers of pupils receiving interventions to support the broad areas of need outlined in government guidelines, little research has asked CYP directly about their experiences of securing and receiving SEND provision or how effective they think the support was for their health and education outcomes. We answered these questions through one-to-one interviews with CYP with SEND.MethodsWe used a semi-structured interview format, structured with a timeline to help participants recount their whole experience. We developed and piloted our approach with a CYP's advisory group. All data collectors were trained by a senior research team. We recruited participants via an online survey about SEND provision in England. Interviews were audio-recorded, transcribed verbatim and anonymized before thematic analysis, complemented by narrative portraiture for selected cases.ResultsWe interviewed 15 CYP aged 13–25 years (12 online, 3 in-person). Respondents had a range of SEND types, most commonly autism. Thematic analysis identified four themes that acted as enablers and barriers to SEND provision: (1) education-based factors; (2) the extent that provision matched need; (3) timing of provision; and (4) relationships, communication and decision-making. Mental health and attainment were the most common outcomes discussed. Our narrative portraitures illustrate the large number and variety of influences on the quality of SEND provision at critical educational stages, which affected their educational, mental health and life trajectories.ConclusionLate identification of SEND, and poor responsiveness of school staff in implementing provision had detrimental consequences for CYP's outcomes. Listening to them about their needs, providing prompt assessments and implementing simple tailored approaches can be hugely beneficial. The ability of CYP and families to advocate for support is a key influence over the quality of provision. Our study has policy implications, including fairer formats for academic assessment and a call for additional SEND training and toolkits for teachers. Further attention must be paid to ensure the needs of all CYP are identified and met, including those who cannot advocate for themselves.